Reducing Risk in Total Joint Arthroplasty: Vascular Status. Issue 3 (September 2019) - Romero, Jose; Westrich, Geoffrey
Abstract : Complications following total joint arthroplasty place a significant burden on patients and the health care system. Patients with vascular disease are at increased risk of perioperative complications and appropriate patient screening and optimization are required to reduce perioperative risks. This article will provide a brief update on the literature and consensus recommendations regarding (1) patients with increased bleeding risk and increased venous thromboembolic event risk, (2) patients with a history of peripheral vascular disease, and (3) patients with lymphedema.